2010
DOI: 10.1007/s12011-010-8778-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cadmium, Chromium, Nickel, and Zinc in Biological Samples of Psoriasis Patients Living in Pakistani Cement Factory Area

Abstract: Psoriasis is a noncontiguous common and chronic skin disorder. The aim of the present study was to compare the level of trace elements cadmium (Cd), chromium (Cr), Nickel (Ni), and zinc (Zn) in biological samples (whole blood, urine, and scalp hair) of psoriasis patients of both gender age ranged (25-55 years) at mild, moderate severe, and more severe stage (n = 418) living in the vicinity of cement factory. For comparison purposes, healthy age-matched referent subjects, residents of industrial and non-industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…Some researchers reported that serum Zn levels were extremely low in psoriasis patients [38][39][40][41]. However Ala et al [5] and Kreft et al [42] did not find a statistically significant difference between psoriasis patients and healthy controls with regard to Zn levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers reported that serum Zn levels were extremely low in psoriasis patients [38][39][40][41]. However Ala et al [5] and Kreft et al [42] did not find a statistically significant difference between psoriasis patients and healthy controls with regard to Zn levels.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is related with several metalloproteins and one fraction in serum (5%) binds to albumin loosely and another binds to globulin (ceruloplasmin) tightly [40]. As ceruloplasmin is an acute phase reactant and more than 90% of serum copper is transferred with ceruloplasmin, elevated Cu levels could only be an inflammation marker [40,44]. Basavaraj et al [18] evaluated Cu levels in psoriasis patients and found that serum Cu levels were higher in both mild and severe groups compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the P95 of Cd was 2.31 lg L À1 in adults living in an industrial area in Tunisia (Khlifi et al, 2014). Mean Cd blood level was 24.10 lg L À1 in Chinese people residing in a polluted area (Wang et al, 2011); 9.81 lg L À1 in adults living in the vicinity of a cement factory in Pakistan (Afridi et al, 2011a); and 1.70 lg L À1 in Korean residents near municipal waste incinerators (Lee et al, 2012).…”
Section: Cadmiummentioning
confidence: 99%
“…A 3-year follow-up study evaluated participants with psoriasis from the Pakistan Cement Factory area. The mean values of cadmium were significantly higher in the scalp, hair, blood, and urine samples of patients with mild and severe psoriasis, as compared with control 46 . However, the Pakistan study has no possible mechanism of interaction and participants were limited to those in the Pakistan Cement Factory area.…”
Section: Discussionmentioning
confidence: 74%